Study of prevalence of genital tract infection in preterm labour and preterm premature rupture of the membranes following fetomaternal outcomes - Bargaje, Ganesh Mahadeo; Hussain, Roshan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Preterm premature rupture of the membranes (PPROM) is a risk factor where loss of amniotic fluid prior to onset of labour in pregnancies <37 weeks of gestation as characterized by a painless flow of fluid from of the vagina, which leads to preterm labour (PTL). The objective was to investigate the prevalence of genital tract infection (GTI) infections in cases with PTL and PPROM, also find the common bacteria isolated in such cases, their sensitivity profile to antibiotics and neonatal outcome in tertiary care hospital located in central India. Methods: A hospital-based prospective observational study was carried out among 60 pregnant women for the period of 1st July 2020 to 30th June 2021. More than half of the pregnant women were presenting as PPROM (53.3%) while a minimum value (46.7%) was presented PTL in the tertiary care hospital at Bhilai, Chhatisgarh. Results: Among the various microorganisms isolated in HVS, a higher value was observed on CoNS (13.33%) followed by Candida sp. (8.33%) and Klebsiella sp. (5.00%) while lower value was observed for Pseudomonas sp. and E. coli (1.67%) among total studied patients. Maximum sensitivity observed with cefepime (66.7%), cefuroxime (55.6%), cefalexin (50.0%), cotrimoxazole (44.0%), vancomycin (44.0%) followed by ampicillin, lincomycin, penicillin, ceftazidime, clindamycin (38.9%) and minimum sensitivity observed with linezolid and teicoplanin (5.6%). Neonatal death did not show any statistically significant association with genital tract infections (GTI). Conclusions: GTI is significant causative factors of PTL and PPROM. It is always suggested to screen and monitor the antenatal women for the presence of asymptomatic GTI infections.